The purpose of the Gospel of Mark in its historical and social context - Roskam, Hendrika Nicoline, 1970- (Novum Testamentum, Supplements, 2004)
This study investigates the issues of the origin and purpose of the Gospel of Mark. The author argues that Mark's Gospel was written in Galilee some time after the Jewish Revolt in 70 AD for a Christian audience that was living under the threat of persecution. The first part of the book examines the situation of Mark's intended readers, and the nature of and reasons for their persecution. The second part establishes in what way the Gospel addresses the situation of Mark's original readers.